Genome Sequence of Enterococcus faecalis NVIT04, Isolated from Nasonia vitripennis - Wang, Guan-Hong (Microbiol Resour Announc, 2019)
Enterococcus faecalis is a Gram-positive, lactic acid-producing coccus which can be found as a member of the gut microbiome in many animal species and is a potential pathogen in humans. Here, we describe the genome sequence of an E. faecalis strain isolated from the gut microbiome of the hymenopteran model Nasonia vitripennis.